The Effect of Educational Mismatch on Wages: A Comparative Study of Migrant and Native Workers - Ferry Maurist Sitorus; Padang Wicaksono (Department of Development Economics, Universitas Sriwijaya, 2021)
One of the important issues in the Indonesian labor market is an educational mismatch. And one of the implications caused by educational mismatch is that the wages received are unsuitable with the educational qualifications have. This study attempts to relate the educational mismatch phenomenon to the issue of internal migration. Hence, this study aimed to reveal the effect of educational mismatch on the earning of workers, especially migrant and native workers. The discussion of educational mismatch was more specific to migrant workers and native workers because these two types of workers had quite different potential earnings. The data used in this research were gained from the National Labor Force Survey (SAKERNAS) in August 2019. The unit of analysis used was workers with labor/employees’ status other than TNI/POLRI aged 15-64 years and over. The results showed that migrant workers were more likely to experience over education than native workers, and native workers were more likely to experience undereducation than migrant workers. Then, based on the results of the multiple linear regression analysis, it was found that migrant workers encountered greater wage penalties than native workers.